Enterotoxin genes in coagulase-negative and coagulase-positive staphylococci isolated from bovine milk - de Freitas Guimarães, Felipe [UNESP]; Nóbrega, Diego Borin [UNESP]; Richini-Pereira, Virginia Bodelão [UNESP]; Marson, Pâmela Merlo [UNESP]; de Figueiredo Pantoja, José Carlos [UNESP]; Langoni, Hélio [UNESP] (American Dairy Science Association, 2013)
The objective of this study was to isolate and identify the main staphylococcal species causing bovine mastitis in 10 Brazilian dairy herds and study their capability to produce enterotoxins. Herds were selected based on size and use of milking technology, and farms were visited once during the study. All mammary glands of all lactating cows were screened using the California Mastitis Test (CMT) and a strip cup. A single aseptic milk sample (20. mL) was collected from all CMT-positive quarters. Identification of Staphylococcus spp. was performed using conventional microbiology, and PCR was used to determine the presence of enterotoxin-encoding genes (sea, seb, sec, and sed). Of the 1,318 CMT-positive milk samples, Staphylococcus spp. were isolated from 263 (19.9%). Of these isolates, 135 (51%) were coagulase-positive staphylococci (CPS) and 128 (49%) were coagulase-negative staphylococci (CNS). Eighteen different species of CNS were isolated, among which S. warneri, S. epidermidis and S. hyicus were the most frequent. The distribution of Staphylococcus species was different among herds: S. epidermidis was found in 8 herds, S. warneri was found in 7 herds, and S. hyicus in 6 herds. Some of the CNS species (S. saprophyticus ssp. saprophyticus, S. auricularis, S. capitis, and S. chromogenes) were isolated in only one of the farms. Genes related to production of enterotoxins were found in 66% (n = 85) of all CNS and in 35% of the CPS isolates. For both CNS and CPS isolates, the most frequently identified enterotoxin genes were sea, seb, and sec; the prevalence of sea differed between CPS (9.5%) and CNS (35.1%) isolates. Staphylococcus warneri isolates showed a greater percentage of sea than seb, sec, or sed, whereas S. hyicus isolates showed a greater percentage of sea than sec. Over 60% of CNS belonged to 3 major species, which carried 62.2 to 81.3% of the enterotoxin genes. The high prevalence highlights the potential for food poisoning caused by these species. For possible high-risk situations for food poisoning, such as milk produced with total bacterial counts greater than regulatory levels and stored under inappropriate temperatures, monitoring contamination with CNS could be important to protect human health. Because the prevalence of CNS intramammary infections in dairy herds is usually high, and these species can be found in great numbers in bulk milk, identification of risk factors for production of staphylococcal enterotoxins should be considered in future studies. © 2013 American Dairy Science Association.
Keywords: Bovine mastitis; Coagulase-negative staphylococci; Enterotoxin gene; Polymerase chain reaction; Bacteria (microorganisms); Bovinae; Staphylococcus; Staphylococcus auricularis; Staphylococcus capitis; Staphylococcus chromogenes; Staphylococcus epidermidis; Staphylococcus hyicus; Staphylococcus saprophyticus; Staphylococcus warneri